2022
DOI: 10.1002/jev2.12196
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Cas9 into extracellular vesicles by protein myristoylation

Abstract: CRISPR/Cas9 genome editing is a very promising avenue for the treatment of a variety of genetic diseases. However, it is still very challenging to encapsulate CRISPR/Cas9 machinery for delivery. Protein N‐myristoylation is an irreversible co/post‐translational modification that results in the covalent attachment of the myristoyl‐group to the N‐terminus of a target protein. It serves as an anchor for a protein to associate with the cell membrane and determines its intracellular trafficking and activity. Extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 79 publications
0
26
0
Order By: Relevance
“…Ran et al produced a stable HEK293T cell line with the EGFP gene inserted into the genome. Upon treatment with CRISPR/Cas9-containing EVs, EGFP expression was significantly reduced, suggesting the function of EV-based DNA editing [ 114 ]. Another lab generated a reporting system in the lung carcinoma cell line A549, where a stop element was added in between the promoter and the DsRed coding sequence.…”
Section: Ev-mediated Crispr/cas9 Delivery For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Ran et al produced a stable HEK293T cell line with the EGFP gene inserted into the genome. Upon treatment with CRISPR/Cas9-containing EVs, EGFP expression was significantly reduced, suggesting the function of EV-based DNA editing [ 114 ]. Another lab generated a reporting system in the lung carcinoma cell line A549, where a stop element was added in between the promoter and the DsRed coding sequence.…”
Section: Ev-mediated Crispr/cas9 Delivery For Cancer Therapymentioning
confidence: 99%
“…This modification added a long carbon chain to the glycine residue of the peptide, serving as a signal to the membrane localization. Intriguingly, 1.47% of total proteins in wild-type EVs were modified with the myristoyl group with unknown functions [ 114 ]. As expected, the myristoylated Cas9 was more likely than the native Cas9 to be sorted within EVs.…”
Section: Ev-mediated Crispr/cas9 Delivery For Cancer Therapymentioning
confidence: 99%
“…Several studies have reported that the recombination of EVs can be achieved by modifying the donor cells [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. In addition, to engineer the construction of EVs, multiple methods for therapeutic molecule loading can be used.…”
Section: Engineering and Recombination Of Apobdsmentioning
confidence: 99%
“…342 Similarly, a more recent study highlighted that myristoylated proteins and the fusion of the octapeptide derived from Src kinase to the N-terminus of the Cas9 protein promotes its encapsulation into EVs. 343 Of more relevance to retinoblastoma, it has been shown that siRNA-loaded onto nanoparticles (targeting survivin) followed by adjuvant chemotherapy showed the capacity to drive tumor cell death in retinoblastoma in vitro. 344 A combination novel approach has been shown that the encapsulation of miR-181a and melphalan into about 170 nm lipid nanoparticle decreased retinoblastoma cell counts in an in vivo xenograft retinoblastoma rat model.…”
Section: Gene Editing Biomaterials For the Management Of Retinoblastomamentioning
confidence: 99%
“…342 Similarly, a more recent study highlighted that myristoylated proteins and the fusion of the octapeptide derived from Src kinase to the N-terminus of the Cas9 protein promotes its encapsulation into EVs. 343…”
Section: Gene Editing Biomaterials For the Management Of Retinoblastomamentioning
confidence: 99%